Progression of Tobacco Control Policies : Lessons from the United States and Implications for Global Action - Novotny, Thomas E.; Mamudu, Hadii M. (World Bank, Washington, DC, 2013)
This paper examines the historical experience of tobacco control in the last five decades and shares important lessons of public health interventions to inform current and future tobacco control programs in other countries. The paper is divided into four parts. The first part gives an overview of the political economy, principal influences and interventions in tobacco control in the United States. It stresses the importance of information shocks and the role played by grassroots organizations. The current situation of tobacco control in the United States is further discussed in the second part, with emphasis on the economic case that led to litigation, as well as the response of the industry and the States. The third part focuses on the present efforts of multilaterals like the World Bank, technical United Nation (UN) agencies such as the World Health Organization, in the context of the new global governance structure: the Framework Convention on Tobacco Control (FCTC). The last section discusses lessons learned and provides recommendations for comprehensive tobacco control programs.